2011
DOI: 10.3109/10428194.2011.635859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homoharringtonine on bone marrow CD34 + CD117 + cells in patients with chronic myelogenous leukemia

Abstract: This study investigated the effect of homoharringtonine (HHT) on bone marrow CD34 + CD117 + cells in patients with chronic myelogenous leukemia (CML). Fifty-seven patients with CML who could not receive either imatinib or interferon-α were treated with HHT (n = 31) or hydroxycarbamide (HU) (n = 26) to induce and maintain remission, and bone marrow CD34 + CD117 + cells were assayed with flow cytometry. The proportion of CD34 + CD117 + cells was higher in untreated patients (24.7 ± 6.4%) than in donors (4.4 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…It is also interesting to note that Pho-s causes the reduction in the BM of asynchronous antigen expression CD34 + /CD117 + and it is characteristically observed in acute myelogenous leukaemia (Santana et al, 2006). In addition, Pho-s inhibits the increase of malignant clones in the BM compartment by causing a reduction of CD34 + and Gr-1 + immature myeloid cells (Li et al , 2012). The major importance of these results is that Pho-s inhibits the growth, differentiation and clonal expansion of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that Pho-s causes the reduction in the BM of asynchronous antigen expression CD34 + /CD117 + and it is characteristically observed in acute myelogenous leukaemia (Santana et al, 2006). In addition, Pho-s inhibits the increase of malignant clones in the BM compartment by causing a reduction of CD34 + and Gr-1 + immature myeloid cells (Li et al , 2012). The major importance of these results is that Pho-s inhibits the growth, differentiation and clonal expansion of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to our prior study (20), the relative selectivity of its antileukemia effect may be one of the mechanisms. Using the bone marrow cells from primary diagnosis CML patients, we have found that the cytotoxic intensity and inhibitory action on telomerase of HHT is stronger on BCR-ABL + CD34 + cells than on normal CD34 + cells and the cytotoxicity effect on lymphocytes of HHT is weak (20). In contrast, IM not only inhibits the tyrosine kinase of leukemic cells, but also the tyrosine kinase of lymphocytes.…”
Section: Discussionmentioning
confidence: 94%
“…CD117 is a transmembrane receptor with tyrosine kinase activity and is widely expressed in CD34 + cells including hemtapoietic stem cells and myeloid progenitor cells for their physiological development and survival. The proportion of CD34 + /CD117 + cells is found to be higher in patients with CML in comparison to healthy subjects (203,241). In CML, it is suggested that the upregulation of CD117 on CD34 + progenitor cells is critical in the activation of survival mechanisms independent of BCR-ABL.…”
Section: Biological Identification and Characterisation Of CML Progenmentioning
confidence: 96%